Identification of Dof transcription factors in Dendrobium huoshanense and expression pattern under abiotic stresses - Gu, Fangli; Zhang, Wenwu; Wang, Tingting; He, Xiaomei; Chen, Naifu; Zhang, Yingyu; Song, Cheng (Frontiers in Genetics, 2024)
DNA-binding with one finger (Dof) transcription factors (TFs) are a unique family of TFs found in higher plants that regulate plant responses to light, hormones, and abiotic stresses. The specific involvement of Dof genes in the response to environmental stresses remains unknown in Dendrobium huoshanense. A total of 22 Dof family genes were identified from the D. huoshanense genome. Chromosome location analysis showed that DhDof genes were distributed on 12 chromosomes, with the largest number of Dof genes located on chromosome 8. The phylogenetic tree revealed that DhDofs could be categorized into 11 distinct subgroups. In addition to the common groups, DhDof4, DhDof5, DhDof17, and the AtDof1.4 ortholog were clustered into the B3 subgroup. Group E was a newly identified branch, among which DhDof6, DhDof7, DhDof8, and DhDof9 were in an independent branch. The conserved motifs and gene structure revealed the differences in motif number and composition of DhDofs. The dof domain near the N-terminus was highly conserved and contained a C2-C2-type zinc finger structure linked with four cysteines. Microsynteny and interspecies collinearity revealed gene duplication events and phylogenetic tree among DhDofs. Large-scale gene duplication had not occurred among the DhDofs genes and only in one pair of genes on chromosome 13. Synteny blocks were found more often between D. huoshanense and its relatives and less often between Oryza sativa and Arabidopsis thaliana. Selection pressure analysis indicated that DhDof genes were subject to purifying selection. Expression profiles and correlation analyses revealed that the Dof gene under hormone treatments showed several different expression patterns. DhDof20 and DhDof21 had the highest expression levels and were co-expressed under MeJA induction. The cis-acting element analysis revealed that each DhDof had several regulatory elements involved in plant growth as well as abiotic stresses. qRT-PCR analysis demonstrated that DhDof2 was the main ABA-responsive gene and DhDof7 was the main cold stress-related gene. IAA suppressed the expression of some Dof candidates, and SA inhibited most of the candidate genes. Our results may provide new insights for the further investigation of the Dof genes and the screening of the core stress-resistance genes.